Ecology and seasonality of Pseudo-nitzschia species (Bacillariophyceae) in the northwestern Adriatic Sea over a 30-years period (1988–2020) - GIULIETTI, SONIA; ROMAGNOLI, TIZIANA; CAMPANELLI, ALESSANDRA; TOTTI, CECILIA; ACCORONI, STEFANO (Mediterranean Marine Science, 2021)
The ecology and seasonality of Pseudo-nitzschia species and their contribution to phytoplankton community were analysed for the first time at the coastal station of the LTER-Senigallia-Susak transect (north-western Adriatic Sea) from 1988 to 2020. Species composition was addressed using DNA sequence data obtained from 106 monoclonal strains isolated from January 2018 to January 2020. The mean annual cycle of total phytoplankton in the study period (Feb 1988–Jan 2020) showed maximum abundances in winter followed by other peaks in spring and autumn. Diatoms were the main contributors in terms of abundance during the winter and the spring blooms. The autumn peak was due to phytoflagellates and diatoms. In summer phytoflagellates dominated the community, followed by diatoms and dinoflagellates, which in this season reached their annual maximum. Pseudo-nitzschia spp. represented on average 0.4–17.6% of diatom community, but during their blooms they could reach up to up to 90% of the total diatom abundances with 106 cells l-1. By LM, six different taxa were recognized: Pseudo-nitzschia cf. delicatissima and P. cf. pseudodelicatissima were the most abundant, followed by P. cf. fraudulenta, P. pungens, P. multistriata and P. cf. galaxiae. P. cf. fraudulenta and P. pungens were indicator taxa of winter. P. cf. delicatissima and P. cf. pseudodelicatissima were spring and summer taxa, respectively. P. galaxiae showed maximum abundances in autumn. DNA sequences revealed the presence of two species belonging to the ’P. seriata group’ (i.e. P. fraudulenta and P. pungens) and four species belonging to the ‘P. delicatissima group’ (P. calliantha and P. mannii within the P. pseudodelicatissima species complex, and P. delicatissima and P. cf. arenysensis within the P. delicatissima species complex). The presence of several cryptic and pseudo-cryptic species highlights the need to combine LM observations with DNA sequence data when the ecology of Pseudo-nitzschia is investigated.